The Contest, the Collation and then the Controversy: an analysis of Ghana’s 2020 Elections - Manboah-Rockson, Joseph Kwabena (Eximia, 2022)
This paper evaluates the impact of a substandard parliamentary and presidential election. Using Ghana as a case study, it analyses the 2020 election and thereafter. The paper is of the view that elections are contested and won at the polling stations when conducted in a free and fair manner. But where a country holds regular multiparty elections at the national level, yet violate liberal-democratic minimum standards in systematic and profound ways, the exercise amounts to a decoy behind institutional facades of representative democracy. For Ghana to consolidate its democratic credentials, its future elections must give legality to the state reflected in Principle II (1) of the African Union’s Principles of Governing Democratic Elections (AU Democratic Principles: AHG/Dec.1 (XXXVIII), which underscores that democratic elections are the basis of the authority of any representative Government.